Acquisition of T-shaped expertise: an exploratory study. (4th March 2017) - Conley, Shannon Nicole; Foley, Rider W.; Gorman, Michael E.; Denham, Jessica; Coleman, Kevin
Abstract: Disciplinary boundaries become increasingly unclear when grappling with "wicked problems, " which present a complex set of policy, cultural, technological, and scientific dimensions. "T-shaped" professionals, i.e. individuals with a depth and breadth of expertise, are being called upon to play a critical role in complex problem-solving. This paper unpacks the notion of the "T-shaped expert" and seeks to situate it within the broader academic literature on expertise, integration, and developmental learning. A component of this project includes an exploratory study, which is aimed at evaluating the emergent attributes of T-shaped expertise in two different educational programs completed between January and May in 2015. The two programs build disciplinary knowledge in science, technology engineering, and mathematics fields at the core (vertical dimension), while expanding the students' awareness and comprehension of other expertise (horizontal dimension). The courses introduced science and engineering students to case study topics focusing around complex human-technological-ecological systems in a nanotechnology and society course; and the governance of genetically modified organisms (GMOs) in a science, technology, and society course. We analyze pre- and post-test data from this pilot project before presenting findings that pertain to student learning, as well as variants in the methodology and reflect on the utility (and limitations) of the selected methodology for evaluating expertise as it evolves over time. The paper closes with a discussion of a theory of acquisition with implications for delineating early attributes and characteristics of T-shaped expertise.